Sentiment Analysis: Sekolah Tatap Muka in the New Normal Era - Suprianto Suprianto; Risma Niswaty; Sitti Hardiyanti Arhas; Nawir Rahman; Rudi Salam (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Through the Circular of the Minister of Education, Culture, Research, and Technology (Mendikbudristek) Number 3 of 2022, face-to-face learning is limited to educational units following the provisions stipulated in the Joint Decree of the Four Ministers. In addition, it is explained that parents/guardians of students are given the choice to permit their children to take part in Limited face-to-face learning or distance learning. This study aimed to determine public sentiment regarding Sekolah Tatap Muka. To achieve the research objectives, sentiment analysis is used using the Drone Emprit application. Data collection was obtained from the Twitter social media application, the data obtained were posts from February 1, 2022, to March 31, 2022. The results showed that there were 898 tweets or 29.23 percent of positive sentiments about sekolah tatap muka, and there were 1,954 tweets or 63.61 percent of negative sentiments about sekolah tatap muka, and there were 220 tweets or 7.16 percent of neutral sentiments about sekolah tatap muka.